Respuesta :
We are given
f(x) = (x + 4)^(x - 2) + 2
g(x) = 8 (20)^x
j(x) is the given data
We are asked to arrange the functions according to increasing y-intercept. Simply substitute 0 to x and solve for the y-intercept. Doing this, the answer is
C.) f(x), g(x),j(x),h(x)
f(x) = (x + 4)^(x - 2) + 2
g(x) = 8 (20)^x
j(x) is the given data
We are asked to arrange the functions according to increasing y-intercept. Simply substitute 0 to x and solve for the y-intercept. Doing this, the answer is
C.) f(x), g(x),j(x),h(x)
The y-intercept of j(x) >y-intercept of g(x) > y-intercept of f(x).
How to calculate the y-intercept?
For y-intercept put x=0 in the given function.
[tex]f(x) = 4^{x-2}[/tex]
For y-intercept put x=0 in f(x)
The y-intercept of f(x)= [tex]4^{0-2}[/tex] = 1/16
[tex]g(x) = 8(20)^x[/tex]
For y-intercept put x=0 in g(x)
The y-intercept of g(x)= [tex]8(20)^0[/tex]=1
Since the decay of the population is exponential in nature, so let us consider:
[tex]j(x) = ab^x[/tex]
From the table, j(1) =8, j(2) =4, j(3) =2
so, [tex]8=ab[/tex]...(1)
[tex]4 =ab^2[/tex].....(2)
[tex]2=ab^3[/tex].....(3)
From (1), (2), and (3)
b=1/2
a =16
So, [tex]j(x) = 16(\frac{1}{2} )^x[/tex]
So, y-intercept of j(x) = [tex]16(\frac{1}{2} )^0[/tex]=16
The y-intercept of j(x) = 16
The y-intercept of g(x) =1
The y-intercept of f(x) =1/16
Therefore, the y-intercept of j(x) >y-intercept of g(x) > y-intercept of f(x).
To get more about functions visit:
https://brainly.com/question/17043948